Direct evidence for radiative charge transfer after inner-shell excitation and ionization of large clusters - Hans, Andreas; Stumpf, Vasili (New journal of physics, 2018)
We directly observe radiative charge transfer (RCT) in Ne clusters by dispersed vacuum-ultraviolet photon detection. The doubly ionized Ne2+- initial states of RCT are populated after resonant 1s-3p photoexcitation or 1s photoionization of Ne n clusters with . These states relax further producing Ne+-Ne+- final states, and the RCT photon is emitted. Ab initio calculations assign the observed RCT signal to the initial state, while transitions from other possible initial states are proposed to be quenched by competing relaxation processes. The present results are in agreement with the commonly discussed scenario, where the doubly ionized atom in a noble gas cluster forms a dimer which dissipates its vibrational energy on a picosecond timescale. Our study complements the picture of the RCT process in weakly bound clusters, providing information which is inaccessible by charged particle detection techniques.